PENGARUH HARGA, PROMOSI DAN TEMPAT TERHADAP KEPUTUSAN PEMBELIAN PADA KFC MEGA - TAHRIN, VEBI SARAH (JURNAL ADMINISTRASI PUBLIK, 2020)
Marketing management is a series of processes of analysis, planning, implementation, andsupervision and control of a marketing activity where the aim is to achieve company targetseffectively and efficiently. Philip Kotler (1980) According to, marketing management is theprocess of analyzing, planning, implementing, and controlling programs. a program thataims to create an exchange with the intended market with a view to achieving company goals,a Marketing Mix is a collection of several variables that a company has used to influenceconsumer responses. Some of these variables include; Prices, Promotions and Places ThatAffect Food Purchasing Decisions at KFC Mega Mall Manado